Full-Bridge ZVS-PWM Hybrid Switched-Capacitor Isolated DC-DC Converter - Anderson Alves; Ivo Barbi (Eletrônica de Potência)
This paper presents a new hybrid switched-capacitor (HSC) isolated DC-DC converter topology generated from the integration of the ladder switching cell with the full-bridge ZVS-PWM converter. This new topology reduces the voltage stress on the switches and other components on the primary side of the transformer to half of the bus voltage, spontaneously equalizes the voltage in the divider capacitors and presents zero-voltage-switching (ZVS) in all switches for a wide load range. The principle of operation, static gain, current stress in the power semiconductors, and commutation analysis are presented in this paper. A theoretical and experimental comparative analysis of the new topology with the TL-NPC converter is also performed. Experimental results with a laboratory prototype with 2 kW rated power, 800 V input voltage, 60 V output voltage and 100 kHz switching frequency show a maximum efficiency of 97.12% for the HSC converter against 96.49% for the TL-NPC converter.